2012
DOI: 10.1080/13546805.2012.663162
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous bodily-self experiences among recreational ketamine users

Abstract: The results corroborate this structural model of out-of-body phenomena and encourage a framework for future studies into aetiological mechanisms of out-of-body experiences to include neurochemical systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…At plasma concentrations ranging from 50 to 200 ng/ml (0.21-0.84 mM; Bowdle et al, 1998), ketamine dose dependently enhances sensory perception (i.e., intensity of sound), emotional connectedness, feelings of unreality, and out-of-body experiences, and may be associated with visual Ketamine and Ketamine Metabolite Pharmacology hallucinations, altered perceptions of self and time, and floating sensations (Hansen et al, 1988;Bowdle et al, 1998;Jansen, 2000;Muetzelfeldt et al, 2008;Wilkins et al, 2012). Undesired effects reported by illicit users include dizziness, blurred vision, slurred speech, vomiting, palpitations, and chest pain (Siegel, 1978;Dalgarno and Shewan, 1996;Weiner et al, 2000;Muetzelfeldt et al, 2008); see section on peripheral effects below.…”
Section: Clinical Effectsmentioning
confidence: 99%
“…At plasma concentrations ranging from 50 to 200 ng/ml (0.21-0.84 mM; Bowdle et al, 1998), ketamine dose dependently enhances sensory perception (i.e., intensity of sound), emotional connectedness, feelings of unreality, and out-of-body experiences, and may be associated with visual Ketamine and Ketamine Metabolite Pharmacology hallucinations, altered perceptions of self and time, and floating sensations (Hansen et al, 1988;Bowdle et al, 1998;Jansen, 2000;Muetzelfeldt et al, 2008;Wilkins et al, 2012). Undesired effects reported by illicit users include dizziness, blurred vision, slurred speech, vomiting, palpitations, and chest pain (Siegel, 1978;Dalgarno and Shewan, 1996;Weiner et al, 2000;Muetzelfeldt et al, 2008); see section on peripheral effects below.…”
Section: Clinical Effectsmentioning
confidence: 99%
“…For example, Varnhagen and Zumbo (1990) found that student learning of statistical concepts was difficult to affect directly through instruction; however, the educational format (i.e., instructional treatment) influenced a mediator (i.e., student attitude) and had an indirect effect on the outcome (i.e., student performance) through a mediational process. Although it has not received as much attention outside of the social sciences, mediation analysis is of growing interest in the other fields such as psychiatry (Meyer-Lindenberg & Weinberger, 2006), neurobiology (Stoltenberg et al 2002), behavior genetics (Munafò, 2006), neuropsychiatry (Wilkins, Girard, & Cheyne, 2012), experimental gerontology (Barger, Kayo, Pugh, Prolla, &Weindruch, 2008), gene expression studies (Allison, Heo, Schork, Wong, & Elston, 2002), health behavior (Veitch et al, 2012), nutrition (Hanks et al, 2010; Forestell & Mennella, 2012), ophthalmology (Popescu et al, 2012), pain management (Meulders, Vansteenwegen, & Vlaeyen, 2012) and quality-of-life research (Cox et al, 2011;).…”
Section: Introductionmentioning
confidence: 99%
“…the impression of being 'teleported' outside of a body to another location in space; ii) the impression of seeing the world from a different visuo-spatial perspective; and iii) the impression of seeing a body from this new perspective (Bunning & Blanke, 2005). This phenomenon is can be observed in some patients with neurological (Blanke, Landis, Spinelli, & Seeck, 2004) and psychiatric (Simeon, 2004) conditions as well as drug abuse (Wilkins, Girard, & Cheyne, 2012). Ehrsson (2007) demonstrated that it is possible to experimentally generate an out-ofbody experience in healthy participants in a systematic manner using virtual reality and tactile stimulation (Fig.…”
Section: Fmri and Out-of-body Experiencesmentioning
confidence: 99%